2019
DOI: 10.1111/tbed.13426
|View full text |Cite
|
Sign up to set email alerts
|

Emerging strains of porcine epidemic diarrhoea virus (PEDv) in Mexico

Abstract: As an emerging disease, the porcine epidemic diarrhoea virus has caused substantial economic losses to the pork industry in Mexico, leading to piglet mortality rates of up to 100%. For detection, sequencing and genetic characterization of the virus, 68 samples of one‐week‐old piglets from pork farms in 17 states of Mexico were analysed. In total, 53 samples were positive by real‐time RT‐PCR, confirming the presence of the virus in 15 states. Twenty‐eight samples from 10 states were amplified by endpoint RT‐PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“… 2015 ; Niederwerder and Hesse 2018 ; Reveles-Felix et al. 2020 ). According to the most recent prevalence study in China, the average PEDV-positive rate in pigs from 39 farms across eight provinces, primarily in Hunan, was 38.0% (Tan et al.…”
Section: Occurrence and Epidemiologymentioning
confidence: 99%
“… 2015 ; Niederwerder and Hesse 2018 ; Reveles-Felix et al. 2020 ). According to the most recent prevalence study in China, the average PEDV-positive rate in pigs from 39 farms across eight provinces, primarily in Hunan, was 38.0% (Tan et al.…”
Section: Occurrence and Epidemiologymentioning
confidence: 99%
“…The infection affects pigs of all ages, with piglets less than one week old being the most affected (100% morbidity and mortality). Although the virus does not affect human health, it causes significant economic losses to the pig breeding industry [ 1 ]. Current treatment is primarily aimed at diarrhea controlling.…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, an outbreak occurred in pigs of all ages in the United States, with the incidence among suckling piglets being as high as 90% [ 11 , 12 ]. Subsequently, PEDV was prevalent in Canada, Mexico, and other counties [ 13 , 14 , 15 , 16 ]. Existing studies have reported that PEDV can exist in transported feeds for a long time, which increases the possibility of its transmission [ 17 ].…”
Section: Introductionmentioning
confidence: 99%